Políticas de rotación del personal en el Supermercado Mayra Loaiza del cantón de Ventanas - Bonilla Garcia, Ginger Elizabeth (2021)
The supermarket "Mayra Loaiza" is located in the canton of Ventanas in the province of Los Rios, has several branches established in different parts of the city, currently passing an internal crisis at the labor level, which is why this case study was chosen. The objective of the study was to evaluate the personnel rotation policies of the supermarket "Mayra Loaiza. The method applied for this research is of descriptive approach, to recognize the variables that intervene in this dysfunction; the techniques applied were an interview directed to the head of the place and a survey applied to 11 servers of the mentioned market. Where it was possible to conclude that, according to the perception of the employees, there is a deficiency in the commitment of the worker for different causes, among them the most highlighted; they are labor stress, insufficient training to the personnel, constant change of personnel, they also mentioned that there is not enough motivation for the workers to perform their work activities with enthusiasm, added to this that the manager prefers to maintain distance between the labor relationship of boss and subordinates. These factors were identified so that managers could take into consideration the need to develop strategies to improve the disadvantages of the supermarket, and thus ensure the successful development of the site and quality customer service.